DIFFERENCES AMONG THE PERCEPTIONS OF ORTHODONTISTS, PROSTHODONTISTS AND CONSERVATIVE DENTISTRY SPECIALISTS REGARDING BUCCAL CORRIDOR WIDTHS - Muhammad Azeem; Ali Raza; Rashid Mahmood; Erum Behroz (Journal of University Medical & Dental College, 2021)
ABSTRACTBACKGROUND & OBJECTIVE: To find out the optimal ranges of smile attractiveness on basis of different amounts of buccal corridor widths, as judged by Pakistani orthodontists, prosthodontists and conservative dentistry specialists (CDS).METHODOLOGY: Present cross-sectional study was conducted from June 2016 to June 2017. The anterior smiling image of a female model was edited to be converted to 10 images displaying different amounts of buccal corridor width. After informed consent from the subject, different buccal corridors widths images were created at following widths: 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, and 18%. This was followed by measurement of smile attractiveness of these 10 images on a visual analogue scale by 30 evaluators in three groups. Group 1 consisted of 10 CDS, group 2 consisted of 10 prosthodontists and group 3 consisted of 10 orthodontists. The data was collected and scores of smile attractiveness were presented in form of mean and standard deviation for each group. The differences in the three groups regarding perception of smile attractiveness were found out using ANOVA test and Turkey’s post-hoc test was used for multiple comparisons.RESULTS: For group 1, the highest scoring was obtained by image showing 10% buccal corridor width. In group 2, the highest score was by image showing 14% buccal corridor width, whereas in group 3, the highest scoring was showing 12% buccal corridor width. The differences found were statistically insignificant.CONCLUSION: Dental specialty does not affect perception of smile attractiveness. Buccal corridor width greater than 14% should be avoided.